Appendicitis with Periappendiceal Abscess and Phlegmon in Second Trimester Pregnancy: A Case Report - Kunal Yadav; Krikesh Shrestha; Rajesh Poudel (Journal of Universal College of Medical Sciences, 2024)
There is anatomical, physiological and biochemical changes in all body systems in pregnancy and these changes can be often misinterpreted as pathological. The unreliable nature of complaint reports, examination ﬁndings, and laboratory parameters in pregnancy appendicitis cases makes it challenging for physicians to diagnose and manage cases effectively. So, we present a case report with presentation dangling between its typical and atypical form.